The ACTN3 gene and its relationship with muscle strength as an indicator for the selection of wrestlers - Saad, A. H. (International Journal of Wrestling Science, 2013)
This study aims to identify the relationship between the ACTN3 gene, maximum strength and explosive power, utilizing maximum strength tests, and some explosive power tests. The sample of this study consisted of 9 subjects, 8 of whom were cadet beginner wrestlers (between the age of 12-14 years), in addition was one adult international level wrestler. To test whether this gene has the ability to predict the wrestler's level of muscle strength we compared the lengths of the gene under study in the beginners and the international wrestler by using restriction enzymes. The main results indicated that there are 8 enzymes that succeeded in differentiating between the international wrestler and junior wrestlers in the length of this gene, while 4 did not succeed. The results also indicated that the gene ACTN3 (R577X) can predict the expected level of muscle strength of the cadet wrestlers, as there were 2 cadets with a ACTN3 gene length similar to the international level wrestler. The similarity in the constituent amino acids for muscle protein was also observed, along with the existence of a direct relationship between some maximum muscle strength and explosive power tests and the length of ACTN3 gene.